Profile and outcomes of symptomatic pancreatic fluid collections at a tertiary care hospital - Addagarla, Varun; Srikanth Kulkarni, Harish; Katepally, Sai Krishna; Kumar, P. Shravan (International Journal of Research in Medical Sciences, 2023)
Background: Pancreatic fluid collections (PFCs) are seen in about 50% cases of pancreatitis. Most PFCs are usually asymptomatic and resolve spontaneously not requiring intervention. However, symptomatic and complicated PFCs require intervention. In this study we aimed at estimating clinical characteristics, demographics, modalities of treatment and their success rates. Methods: 40 patients with symptomatic PFCs were included in this study. Clinical characteristics, type and location of PFC, indication for treatment, type of intervention, their success and complication rates were recorded. Results: Among 40 patients, 29 were male and 11 females with mean age of 40.2±7.5 years. The most common PFC was pseudocyst (62.5%) followed by walled off necrosis (WON) (25%). The most common indication for intervention was abdominal pain (50%) followed by gastric outlet obstruction (25%), obstructive jaundice (15%) and sepsis (10%). The success rate of EUS guided transmural drainage was 95.6% for pseudocyst and 77.7% for WON. The rate of adverse events was 32% in pseudocysts and 40% in WON. DEN (direct endoscopic necrosectomy) was done in 3 cases of infected WON. Conclusions: The most common PFC seen in practice is pseudocyst followed by WON. Endoscopic (EUS guided) transmural drainage has emerged as the first line intervention for symptomatic PFCs. The rate of complications and associated morbidity is much lesser with endoscopic procedures compared to surgery. The success rate of endoscopic intervention is higher in cases of pseudocyst but complications are higher in necrotic collections.